Berlin shuffle : a novel - Boschwitz, Ulrich Alexander, 1915-1942 (Metropolitan Books/Henry Holt and Company, 2025)
"A prophetic lost classic from interwar Germany, now translated into English for the first time, following a group of Berliners on the skids as their nation unravels. Berlin in the 1920s is the largest city in Europe, a cultural mecca, and a political mess: a hedonistic Babylon, though there's little glamour for the hundreds of thousands out of work, the war wounded, the prostitutes, and the beggars. Come evening, they too want to shed their cares at the Jolly Huntsman pub, where they gather to drink, dance, and reassert their pride. But there's always disaster lurking in the alleys and flophouses, a disaster that the twenty-two-year-old author Ulrich Alexander Boschwitz clearly saw coming for his nation. In this dark comedy of petty theft, soapbox speeches, and bar fights is the disarray of a country devouring itself. Tragically, Germany's self-destruction engulfed the author, who was killed five years after finishing this novel. When Boschwitz's The Passenger was rediscovered in 2021, it was heralded as a masterpiece that terrifyingly captured the zeitgeist of life under Nazism. Now, Berlin Shuffle-his literary debut from 1937, finally available in English, with a preface by the preeminent translator Philip Boehm-brings to life the society that would enable fascism's takeover. The triumph of one of world literature's spectacular talents, Berlin Shuffle is a dire warning, sent from a pivotal moment in history to our own time"-- Provided by publisher.